An integrated virtual pathology education platform developed using Microsoft Power Apps and Microsoft Teams - Ajay Rajaram; Carel Olory; Valérie Leduc; Gertruda Evaristo; Kevin Coté; Jordan Isenberg; Julia Schur Isenberg; David Ling Dai; Jason Karamchandani; Moy Fong Chen; Chelsea Maedler-Kron; Pierre Olivier Fiset (Elsevier, 2022)
The transition towards digital pathology and an extensive selection of video conferencing platforms have helped provide continuity to education even during the COVID-19 pandemic. Innovative approaches for pathology education, will likely persist beyond the pandemic, as they have powerful didactic potential. While there is a wide selection of software for use as educational tools, an environment to access all resources with ease is clearly lacking. In this technical note, we highlight our customized educational applications built using a low-code approach. Our applications, developed with Microsoft Power Apps, serve both educational and examination purposes and are launched using Microsoft Teams. Building applications using a low-code approach has made our applications very specific to our use and enabled daily distanced education. Combined with existing features on Teams, such as file sharing, meeting scheduling, and messaging, the applications serve as a unique and customizable pathology educational platform.